Bewegungsförmiger Rechtsextremismus Militia of Montana und Identitäre Bewegung im Vergleich - Kinskofer, Moritz (Young Academics: Politikwissenschaft, 2023)
Right-wing extremism's tendency towards fragmentation and individualisation can be observed more and more frequently. This is also the case with the Militia of Montana and the Identitarian Movement. In this book, Moritz Kinskofer analyses them through the lens of strain theory and compares them in terms of the intensity of their extremism. He identifies resistance to the system, which is perceived as anomic and infiltrated by conspiracies, as central to both movements. Above all, the adaptability of conspiracy myths as well as camouflage mechanisms such as relocation to the internet along with different degrees of organisation and varying dispositions towards violence represent enormous factors that have an impact on their resilience to state persecution.